The Teacher-Student Relationship from a Gramscian Perspective - Rene Trentin Silveira (Universidade Federal do Rio Grande do Sul, 2018)
The aim of this article is to analyze the teacher-student relationship in light of Gramscian categories. To do so, a Gramsci's newspaper article published in 1915; some notes from the Prison Notebooks; and a letter to his brother Carlo, written in 1930, are used as references. It is intended to demonstrate that the author argues in favour of a friendly relationship between teacher and student, which would exclude pedagogic spontaneity as much as authoritarianism, psittacism and dilettantism. In short, to Gramsci, the nature of the teacher-student relationship is dialectic, in such a way that "every teacher is always a student and every student is a teacher" (Gramsci, 2001, p. 399). This conception is articulated with the author's ideas on the relationship between intellectuals and the masses and about the question of hegemony.